Activity cycles of national Rugby League and national Youth Competition matches - Gabbett, T. J. (The Journal of Strength and Conditioning Research, 2012)
Examination of ball-in-play periods (i.e., match activity cycles) is a method used to provide insight into the physical demands of team sport competition. However, to date, no study has investigated the ball-in-play time of rugby league matches. This study investigated the activity cycles (i.e., ball-in-play periods) of elite National Rugby League (NRL) and National Youth Competition (NYC) matches. Video recordings of 393 NRL matches and 388 NYC matches were coded for activity and recovery cycles. Time when the ball was continuously in play was considered activity, whereas any stoppages during the match (e.g., for scrums, penalties, line drop-outs, tries, and video referee decisions) were considered recovery. The total time the ball was in play for NRL and NYC matches was approximately 55 minutes and 50 minutes, respectively. In comparison with NYC matches, NRL matches had longer average activity cycles (81.2 ± 16.1 vs. 72.0 ± 14.7 seconds, effect size [ES] = 0.60). The average longest activity cycle was also higher (ES = 0.48) in NRL (318.3 ± 65.4 seconds) than in NYC (288.9 ± 57.5 seconds) matches. The longest activity cycle from any match was 667 and 701 seconds for NRL and NYC matches, respectively. The NRL matches had a smaller proportion of short duration (<45 seconds) activity cycles and a greater proportion of longer duration (>91-600 seconds) activity cycles. In conclusion, meaningful differences in activity cycles were observed between NRL and NYC matches, with NRL competition demonstrating longer ball-in-play periods, a smaller proportion of short duration activity cycles, and a larger proportion of longer duration activity cycles. These findings suggest that the ability to perform prolonged high-intensity exercise, coupled with the capacity to recover during brief stoppages in play, is a critical requirement of professional rugby league match play.